Principles of Good Governance: Operational Management Direct Expenditure and Tax Services in General Affairs Division Secretariat of Local People's Representative Council (DPRD) West Java Province, Indonesia - Anggi Nurani Rahmat; Andre Ariesmansyah; Triana Andariah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The implementation of good governance in the operational service management of direct spending and tax documents in the General Section of the Secretariat of the West Java Provincial People's Representative Council is very important to do. This aims to improve the quality of public services, transparency, accountability, and effectiveness of the use of public funds. This study aims to analyze the implementation of good governance principles in organizing the service of shopping documents and direct spending taxes in the General Section of the Secretariat of the West Java Provincial DPRD. The implementation of the principles of transparency, accountability, and community participation is believed to be able to encourage an increase in the quality of public services